A study of emotional intelligence and perceived parenting styles among adolescents in a rural area in Karnataka - Neethu George; Deepthi N Shanbhag; Meera George; Ann Christy Shaju; Reuben C Johnson; P Thomas Mathew; Chaitanya Prasad Golapalli; Ramakrishna Goud (Journal of Family Medicine and Primary Care, 2017)
Context: Adolescence is the time which is crucial for the overall development of a person both mentally and physically. In this period, along with academic intelligence, emotional intelligence (EI) also plays an equal or strong role in student life. Aims: This study was to assess EI, parental bonding, and their association among adolescents in high schools under Sarjapur PHC area. Subjects and Methods: This was a cross-sectional study conducted among high school students under Sarjapur PHC area. The EI was assessed using EI scale which measured self-awareness, self-regulation, motivation, empathy, and social skills. The parental bonding instrument was utilized to determine the parental styles of both the parents and was interpreted in terms of care and protection as neglectful parenting, affectionless control, optimal parenting, and affectionate control. Results: A total of 300 adolescents were interviewed. It was seen that most of them had low EI in self-awareness, i.e., 92 (30.7%), motivation 99 (33%), and social skills 101 (33.7%). It was also observed that most of them had high EI in self-regulation, i.e., 98 (32.7%) and moderately high EI in empathy 117 (39%). The study group perceived that 147 (49%) of the fathers and 109 (36.3%) of the mothers had affectionless control. Conclusion: Along with poor parenting, most of the respondents also have low EI in self-awareness, motivation, and social skills which has to be addressed for the future of the country.